Comparative analysis of noise immunity of the information transmission channel of secondary radar systems - Svyd, I.V.; Vorgul, I.Yu.; Starokozhev, S.V.; Tkach, M.G.; Maltsev, O.S.; Shevtsov , I.O. (Radiotekhnika, 2022)
This paper presents the conducted assessment of noise immunity of the request signal transmission channel and response channel for flight information of secondary radar systems as part of aircraft responders. The considered system is an open single-channel queuing system with refusing due to the action in the request channel of intentional and unintentional correlated and uncorrelated (intra-system) interference and ground-based receivers that receive, process and decode flight information in the presence of fluctuation and intra-system interference in the receiving channel. The results of assessing the noise immunity of the aircraft responder in the form of the aircraft responder’s readiness factor under the action of internal and deliberate interference are given. It is shown that the principle of constructing an aircraft responder and the principle of servicing request signals and transmitting flight information do not allow ensuring acceptable probabilities of obtaining flight data at ground control points.